Management of Postburn Contracture Neck Using Pectoralis Major Myocutaneous Flap - Dr. V. Bhattacharya; Dr. J. K. Sinha; Dr. F. M. Tripathi; Dr. J. M. Das (Indian Journal of Plastic Surgery)
The use of pectoralis major myocutaneous flap for the management of post-burn contracture of neck is described. Its merits and demerits are discussed.